The Effect of Professional Skepticism on Fraud Detection with Auditor Training as a Moderating Variable - Husnah, Hermini Nur; Sari, Ratna; Mapparenta, Mapparenta (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study examines professional skepticism's effect on fraud detection, focusing on auditor training as a moderating variable within the Inspectorate of South Sulawesi Province. Research Design and Methodology: The research adopts a quantitative approach, utilizing primary data collected through questionnaires distributed to auditors at the regional inspectorate office, employing a census sampling technique. The sample consists of 40 auditors. Structural Equation Modeling (SEM) was employed using the Smart PLS application to test the hypotheses. Findings and Discussion: The study reveals that professional skepticism positively and significantly impacts fraud detection. Additionally, auditor training is found to moderate this relationship, strengthening the influence of professional skepticism on an auditor’s ability to detect fraud. These findings suggest that targeted auditor training and a higher level of professional skepticism increase the efficacy of fraud detection efforts. Implications: The findings have practical implications for audit practices and management policies, particularly in governmental auditing contexts. Enhancing professional skepticism through training programs can significantly improve auditors' capacity to detect fraud and safeguard public resources. This study underscores the importance of integrating continuous professional development with a skeptical mindset to enhance audit quality and integrity.